Effect of ultrasound-assisted extraction of Moringa stenopetala leaves on bioactive compounds and their antioxidant activity - Dadi, Debebe Worku (Array, 2019)
Moringa stenopetala is a multipurpose plant having high nutritional and medicinal values. The aim of this study is to evaluate the effect of time and temperature of ultrasound-assisted extraction on bioactive compounds and antioxidant activities of M. stenopetala leaf extract. The ultrasound-assisted extraction took place at each of 30, 40 and 50 °C for 10, 20 and 30 min. The study also included the analysis of the interaction effects of time and temperature on the total phenolic content, total flavonoid content, antioxidant activity (ABTS and DPPH assay), FRAP and chelating activity. The highest total phenolic content, expressed in mg gallic acid equivalents per g dry mass, was 46.6 and total flavonoid content, expressed in mg catechin equivalents per g dry mass, was 20.4 at 40 °C for 20 min. Under the same conditions, the highest antioxidant activities evaluated by DPPH, ABTS and FRAP, expressed in mg Trolox equivalents per g dry mass, were 336.5, 581.8 and 133.3 respectively, and chelating activity, expressed in mg EDTA equivalents per g dry mass, was 28.4. The lowest amounts of bioactive compounds and antioxidant activities were observable when the extraction occurred at 50 °C for 30 min, followed by the extraction at lower temperature (30 °C) for shorter time (10 min). The morphological analysis of the residues obtained after extraction using scanning electron microscope indicated that there was a higher ultrasonic destruction of the structural components of the sample at longer extraction time. Therefore, ultrasound-assisted extraction at a temperature of 40 °C for 20 min is the best time-temperature combination to extract bioactive compounds from M. stenopetala leaves.